Unicellular Cyanobacteria Are Important Components of Phytoplankton Communities in Australia’s Northern Oceanic Ecoregions - Moore, Lisa R.; Huang, Taotao; Ostrowski, Martin; Mazard, Sophie; Kumar, Sheemal S.; Gamage, Hasinika K. A. H.; Brown, Mark V.; Messer, Lauren F.; Seymour, Justin R.; Paulsen, Ian T. (Frontiers in Microbiology, 2019)
The tropical marine environments of northern Australia encompasses a diverse range of geomorphological and oceanographic conditions and high levels of productivity and nitrogen fixation. However, efforts to characterise phytoplankton assemblages in these waters have been restricted to studies using microscopic and pigment analyses, leading to the current consensus that this region is dominated by large diatoms, dinoflagellates and the marine cyanobacterium Trichodesmium. During an oceanographic transect from the Arafura Sea through the Torres Strait to the Coral Sea, we characterised prokaryotic and eukaryotic phytoplankton communities using a combination of flow cytometry and Illumina based 16S and 18S ribosomal RNA amplicon sequencing. Contrary to previous reports, phytoplankton assemblages throughout the entire region were rich in unicellular cyanobacterial primary producers while photosynthetic eukaryotes formed a consistent, though smaller proportion of the photosynthetic biomass. Major taxonomic groups displayed distinct biogeographic patterns linked to oceanographic and nutrient conditions. Cyanobacteria dominated in both flow cytometric abundance and carbon biomass, with members of the Synechococcus genus dominating in the shallower Arafura Sea and Torres Strait where chlorophyll was relatively higher (averaging 0.4 ± 0.2 mg m-3), and Prochlorococcus dominating in the oligotrophic Coral Sea where chlorophyll averaged 0.13 ± 0.07 mg m-3. More consistent with previous observations, we found that a variety of diatoms (Bacillariophyceae) exhibited high relative abundance in the Arafura Sea and Torres Strait, while dinoflagellates (Dinophyceae) and prymnesiophytes (Prymnesiophyceae) were more abundant in the Coral Sea. Ordination analysis identified temperature, nutrient concentrations and water depth as key drivers of assemblage composition. This is the first comprehensive molecular survey of the abundance and diversity of both prokaryotic and eukaryotic phytoplankton in this region, and points to the need to include the picocyanobacterial populations as an essential oceanic variable for sustained monitoring in order to better understand the health of these important coastal waters as global oceans change.